Writing in your own voice: An intervention that reduces plagiarism and common writing problems in students' scientific writing. Issue 5 (21st June 2019) - Yang, Anqi; Stockwell, Sarah; McDonnell, Lisa
Abstract: In many of our courses, particularly laboratory courses, students are expected to engage in scientific writing. Despite various efforts by other courses and library resources, as instructors we are often faced with the frustration of student plagiarism and related writing problems. Here, we describe a simple Writing in Your Own Voice intervention designed to help students become more aware of different types of plagiarism and writing problems, avoid those problems, and practice writing in their own voice. In this article, we will introduce the types of plagiarism and writing problems commonly encountered in our molecular biology laboratory course, the intervention, and the results of our study. From the evaluation of 365 student reports, we found the intervention resulted in nearly 50% fewer instances of plagiarism and common writing problems. We also observed significantly fewer instances of severe plagiarism (e.g. several sentences copied from an external source). In addition, we find that the effects last for several weeks after the students complete the intervention assignment. This assignment is particularly easy to implement and can be a very useful tool for teaching students how to write in their own voices. © 2019 International Union of Biochemistry and Molecular Biology, 47(5):589–598, 2019.